The Cambridge companion to William James - Putnam, Ruth Anna (Cambridge : Cambridge University Press, 1997)
James was both a philosopher and a psychologist, nowadays most closely associated with the pragmatic theory of truth. These essays deal with the full range of his thought as well as other issues of his time.
Introduction / Ruth Anna Putnam --Pragmatism and introspective psychology / Gerald E. Myers--Consciousness as a pragmatist views it / Owen Flanagan --John Dewey's naturalization of William James / Richard M. Gale --James, Clifford, and the scientific conscience / David A. Hollinger--Religious faith, intellectual responsibility, and romance / Richard Rorty --The breathtaking intimacy of the material world / Bruce Wilshire--James, aboutness, and his British critics / T.L.S. Sprigge--Logical principles and philosophical attitudes / Christopher Hookway --James's theory of truth / Hilary Putnam --The James/Royce dispute and the development of Jarnests "solution" / James Conant--William James on religious experience / Richard R. Niebuhr --Interpreting the universe after a social analogy / David C. Lamberth --Moral philosophy and the development of morality / Graham H. Bird --Some of life's ideals / Ruth Anna Putnam --A shelter of the mind / Jessica R. Feldman--The influence of William James on American culture / Ross Posnock --Pragmatism, politics, and the corridor / Harvey J. Cormier --James and the Kantian tradition / Thomas Carlson.
Includes bibliographical references and index
Keywords: James, William, 1842-1910